2019
DOI: 10.1097/md.0000000000014930
|View full text |Cite
|
Sign up to set email alerts
|

Mid-arm circumference, body fat, nutritional and inflammatory biomarkers, blood glucose, dialysis adequacy influence all-cause mortality in hemodialysis patients

Abstract: Hemodialysis patients are at the high risk for morbidity and mortality. Evaluation and management of body composition and biochemical values are important to improve dialysis outcomes. We aimed to examine the effects of the mid-arm circumference, body fat, nutritional and inflammatory biomarkers, blood glucose, and dialysis adequacy on the mortality. A prospective cohort study was conducted on 375 patients from 7 hospital-based dialysis centers. At baseline between September 2013 and April 2017, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 41 publications
2
15
0
1
Order By: Relevance
“…The most important finding of the current study is that a higher percent body fat was significantly associated with lower risk for all-cause mortality in the overall sample, and in patients with elevated HOMA-IR. In previous studies, body fat (as measured by percent body fat, or fat tissue, or body mass index) has been found to be an independent predictor for longer survival in hemodialysis patients [8,38,39,40,41,42]. In addition, a low baseline PBF and fat loss over time significantly increases mortality in maintenance hemodialysis patients, as found in a previous study [43].…”
Section: Discussionsupporting
confidence: 56%
“…The most important finding of the current study is that a higher percent body fat was significantly associated with lower risk for all-cause mortality in the overall sample, and in patients with elevated HOMA-IR. In previous studies, body fat (as measured by percent body fat, or fat tissue, or body mass index) has been found to be an independent predictor for longer survival in hemodialysis patients [8,38,39,40,41,42]. In addition, a low baseline PBF and fat loss over time significantly increases mortality in maintenance hemodialysis patients, as found in a previous study [43].…”
Section: Discussionsupporting
confidence: 56%
“…Despite constant efforts to improve the survival of hemodialysis (HD) patients, which have produced tangible results, their mortality rate remains high [1, 2]. Several factors affect survival in HD patients, with dialysis adequacy representing one of the most important and modifiable factors [3, 4]. Single-pool Kt/V urea (spKt/V), which is urea clearance multiplied by duration of treatment session and normalized for urea distribution volume, is universally employed as a measure of delivered dialysis dose.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of the individual studies are listed in Table 1, and the selection of this study is elucidated in Figure 1. Six studies reported the relationship between SUA and mortality with peritoneal dialysis (PD) patients [13, 15, 19, 37, 38, 40], while 8 studies had hemodialysis (HD) cohorts [8, 17, 27, 30, 31, 34, 35, 39]. Seventeen studies collected the outcome of cardiovascular mortality.…”
Section: Resultsmentioning
confidence: 99%